2015
DOI: 10.5935/1806-6690.20150025
|View full text |Cite
|
Sign up to set email alerts
|

Diets containing leucaena or estilosantes hay in lactating mixed-breed Anglo-Nubian goats

Abstract: RESUMO -Com o intuito de avaliar dietas para cabras Anglo-Nubianas do tipo misto em lactação, foram utilizadas oito cabras com peso médio 37,9 ± 1,72 kg, entre a 2ª e 4ª ordem de lactação, no terço médio da lactação, distribuídas em duplo quadrado latino 4 x 4. A ordenha foi realizada as 7 e 16 h. Os tratamentos consistiram de quatro dietas formuladas com diferentes volumosos (silagem de capim-elefante associada ou não aos fenos de leucena ou de estilosantes) e milho em grão, acrescidas ou não do farelo de soj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Evaluating the association or not of legume hay with concentrate in goat diets Anglo-Nubiano, Câmara et al (2015) observed that the intake of DM, NDF, ADF and TDN did not differ. The authors associated this response with the fiber content of legumes used, styles and leucine, which are forages with higher fiber content.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the association or not of legume hay with concentrate in goat diets Anglo-Nubiano, Câmara et al (2015) observed that the intake of DM, NDF, ADF and TDN did not differ. The authors associated this response with the fiber content of legumes used, styles and leucine, which are forages with higher fiber content.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are in line with those observed in the literature (Aguerre et al, 2016;Pathak et al, 2017;Min and Solaiman, 2018), in which tannins are shown to be beneficial for ruminants at low concentrations because they protect plant proteins from ruminal degradation. Lactating goats need diets with adequate protein levels to meet the maintenance and production requirements, with a direct impact on the persistence of lactation and the amount of milk produced (Câmara et al, 2015). Although the Repartida goat had a lower intake of CP in relation to the Canindé and Saanen goat, its crude protein requirements were met by the diets, according to what was established by the NRC (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Flourishing in acidic soils, Leucaena demonstrates minimal nutrient requirements, making it an ideal candidate for areas with low soil fertility. Its deep-rooting system enables it to tap into water reserves in deeper soil layers, rendering it resilient to drought conditions [8,31] .…”
Section: Leucaena (Leucaena Leucocephala)mentioning
confidence: 99%